PERAN ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) DALAM PENINGKATAN PENCAPAIAN TUJUAN ORGANISASI: SEBUAH KAJIAN LITERATUR - I Gede Aryana Mahayasa; I Wayan Suartina (JUIMA : JURNAL ILMU MANAJEMEN, 2019)
Increasing competition in various sectors triggered by globalization requiresindustry challenges, methods and business strategies to be able to maintain the existence and sustainability of the business. Behaviorthat providesfreedom that is not part of an employee'sformal work, but contributesto the social and psychological work environment, is called organizational citizenship behavior (OCB). OCB as an individual freedom, which does not directly or explicitly receive appreciation from the imbalance ofthe formal system, and which fully encourages the effectiveness of organizational functions. This study is a literature study that aims to find out OCB and the factors that influence OCB as well as OCB Benefits for organizations. From the literature study on the results of previous empirical research, it is found that OCB findings are very important for improving organizational goals. Job satisfaction factors, organizational commitment, personality, self-efficacy, culture and leadership are very influential factors on OCB. The implementation of OCB is very decisive in organizations through case studies by taking into account the factorsthat influence it in accordancewith organizational goals.